From Financial Distress to Financial Resilience: A Systematic Review of the Determinants and Research Agenda for Oil and Gas Firms in the Energy Transition - Nugroho Setyo Utomo; Hermanto Siregar; Koes Pranowo; Nimmi Zulbainarni (Greenation International Journal of Economics and Accounting, 2026)
The oil and gas (O&G) industry faces a double disruption: structurally higher oil-price volatility and an accelerating net-zero transition that jointly threaten the financial stability of incumbent firms. This study reviews the determinants of financial resilience in O&G firms during the energy transition and consolidates a research agenda. Following the PRISMA 2020 protocol, a Boolean query in Scopus returned 74 records. After removing 5 duplicates and screening 69 records against pre-specified eligibility criteria, 23 studies were retained for synthesis, 22 of them oil-and-gas or energy-firm focused. Evidence was synthesised through an effect-direction matrix and organised with the ADO and TCCM frameworks. The literature converges on a recurrent set of determinants: internally, capital structure and leverage, liquidity, green capital expenditure, and profitability; externally, oil-price volatility, interest rates, and carbon pricing or climate policy. The evidence base remains fragmented and dominated by macro- and policy-level analyses, with limited firm-level dynamic modelling. The review reframes the field from financial distress toward financial resilience, proposes an integrative antecedents–decisions–outcomes framework, and articulates a TCCM-structured research agenda with propositions testable using dynamic panel (GMM) methods.